Monster blood for breakfast! - Stine, R. L. (New York : Scholastic, 2008)
Matt Daniels, an athlete who appreciates the value of a good breakfast, falls for a prank that leaves him inside a horrifying scream park.
Monster blood for breakfast! -- Enter HorrorLand -- Fear file.
3.6
5-8
Keywords: Amusement parks -- Juvenile fiction; Practical jokes -- Juvenile fiction; Amusement parks -- Fiction; Horror stories; Practical jokes -- Fiction; Amusement parks -- Fiction; Horror fiction; Practical jokes -- Fiction; Horror fiction